Online Partial Discharge Measurement As A Predictive Maintenance Tool Of Motor And Generator Stator Windings - Soetjipto Soewono; Better Pasaribu (Eduvest - Journal of Universal Studies, 2022)
Partial discharge data collected from more than hundred-unit machines with rated voltages from 6.3 kV to 28 kV with air and gas hydrogen cooling systems machines. Analysis of partial discharge data was carried out for several machines that were failed in services or on machines where evidence of damages to the stator insulation were found due to partial discharge during a visual inspection or offline test results. This analysis suggests that the increasing trend of partial discharge within a certain period is a very important parameter to know that there is an insulation failure process that is happening to the motor and generator stator. It was found that the θ angle of increasing partial discharge values from 86° - 90° is a critical increase in partial discharges and needs to be followed up immediately. The θ angle of increasing trend is obtained from arctan (Y/X) where X is the time of increasing trend usually in month period and Y is partial discharge's value that increased in the X period in mV. It was also found that each failure mechanism that occurring have different pulse distribution characteristics.